Robot-assisted versus transumbilical laparoendoscopic single-site surgery in gynecological procedures: A retrospective comparative analysis of efficacy - Jiahui Zhao; Yuan Liao; Juyuan Huang; Jing Cheng; Jiaqiang Xiong; Jing Liao; Wei Zhang (Intelligent Surgery)
Objective: To compare perioperative outcomes between R-LESS and TU-LESS in gynecological transabdominal procedures. Methods: A retrospective analysis was conducted on gynecological patients undergone surgery at our institution from January 2020 to December 2024. Cases were stratified into R-LESS (n ​= ​725) and TU-LESS (n ​= ​848) groups, encompassing six surgery types, including total hysterectomy, uterine fibroid resection, ovarian cyst enucleation, ect. Comparative parameters included baseline characteristics, perioperative metrics (duration of surgery, intraoperative blood loss, ect.), and postoperative recovery and laboratory indicators (length of hospital stay, abdominal drain removal time, ect.). Results: In total hysterectomy procedures, the R-LESS group demonstrated significantly lower intraoperative fluid replacement (P<0.001) and reduced blood loss (P ​= ​0.013) compared to the TU-LESS group for benign diseases, albeit with prolonged abdominal drain removal time (P<0.001). For malignant diseases, the R-LESS group exhibited superior intraoperative hemostasis (P ​= ​0.047) and fluid management (P ​= ​0.01), accompanied by more pronounced postoperative WBC elevation (P ​= ​0.009). In uterine fibroid resection, the R-LESS group showed advantages in intraoperative blood loss (P<0.001), intraoperative fluid replacement (P<0.001), and postoperative VAS scores (P ​= ​0.022), as well as in the magnitude of Hb reduction on the first postoperative day (P ​= ​0.003). Simultaneously, it shortened the abdominal drain removal time (P ​= ​0.043), but exhibited a greater WBC elevation magnitude (P ​= ​0.001). Significantly reduced blood loss was observed in R-LESS groups for ovarian cyst resection and combined uterine fibroid and ovarian cyst resection (P<0.05). No statistical differences were noted in ICU admission rates or severe complication incidences between groups (P ​> ​0.05). Conclusion: R-LESS exhibits precision advantages in complex procedures (malignancy lymphadenectomy, deep ovarian cyst enucleation), particularly for high-risk cases requiring meticulous manipulation. TU-LESS retains clinical value in simpler surgeries (unilateral/bilateral adnexectomy, salpingectomy) due to procedural efficiency and cost-effectiveness. Future efforts should focus on optimizing R-LESS workflows to expedite recovery and refine surgery-specific selection criteria.